Prevalence of third and fourth degree of perineal lacerations during vaginal delivery and some related factors in Nik Nafs maternity of Rafsanjan in 2015-2017 - Marzieh Loripour; Marzieh Najar Mohiabadi; Pooran Allahbakhshi Nasab; Ahmadreza Sayadi (Mashhad University of Medical Sciences, 2021)
Introduction: Perineal injury is a common complication of vaginal delivery that can affect women's physical, mental and social health. This study was performed with aim to determine the prevalence of third and fourth degree of perineal laceration during delivery and some related factors. Methods: In this retrospective analytical -descriptive study, information was extracted from the records of mothers who gave birth during 2015-2017. The control group consisted of 129 mothers who did not have severe rupture and were selected by systematic randomization among vaginal deliveries performed during the mentioned years. After collecting information about the factors related to the perineal laceration, data were analyzed by SPSS software (version 18) and Chi-square and Fisher Exact and independent t tests. P<0.05 was considered statistically significant. Results: Among 8814 vaginal deliveries performed during the relevant years, there were 32 cases of third and fourth degree of perineal laceration (0.363%), of these, 22 cases were noli par (68.8%). In comparison between the case (n=32) and control (n=129) groups, the work experience of the delivery agent (p<0.02), instrumental delivery (p<0.023) and the duration of the second stage of labour (p<0.0001) were more in the case group. Conclusion: Third and fourth degree of perineal lacerations are associated with the second stage of longer labour and instrumental labour that requires the presence of a labour agent with a longer work experience.